Constructing Polymetallic Nodes in Metal–Organic Frameworks Enhance Antibacterial of Drug‐Resistant Bacteria - Qinqin Li; Shihan Zhang; Yachao Xu; Yaru Guo; Youxing Liu (Advanced Science)
Abstract The misuse of antibiotics results in the emergence of a large number of drug‐resistant bacteria, which leads to huge financial and social burdens. Exploring artificial nanozymes is regarded as a promising candidates for the substitution of antibiotics, but still remain a huge challenge. Herein, a new strategy is reported for constructing polymetallic indium coordination node Metal‐organic frameworks (MOFs) (polyIn‐BTB) for enhancing the production of reactive oxygen species (ROS), which significantly promote antibacterial activity. Theoretical research reveals that, compared to monometallic indium coordination node MOFs (monoIn‐BTB), polyIn‐BTB exhibits a stronger electron‐donating ability, which can facilitate the efficient production of ROS. Thus, polyIn‐BTB shows outstanding antibacterial properties of 87.0% and 92.0% for Methicillin‐Resistant Staphylococcus aureus (MRS. aureus) and Escherichia coli (E. coli) respectively, which is significantly higher than that of monoIn‐BTB (42% for MRS. Aureus and 50% for E. coli). The in vivo experiments demonstrate that polyIn‐BTB accelerates wound healing by killing bacteria and inhibiting the inflammatory response they cause, with a wound healing rate of 98.0% in 8 days. Overall, this work reports a new strategy for constructing polyIn‐BTB for enhancing the antibacterial performance, which opens the door to fundamental research on designing the nanozyme with high performance.